Characterization of multi-wall carbon nanotube/multi- layer graphene fibre-reinforced solder alloy composites - Ghamarian, Nima (2017)
In this study, the metallurgical effect of multi-wall carbon nanotube (MWCNT) and multi-layer graphene (MLG) on the eutectic Bi-Ag alloy were explored. Plain Bi-2.5Ag and its reinforced solder systems (Bi-2.5Ag + xMWCNT/ xMLG, x= 0.01, 0.03, 0.05, 0.07 and 0.1 wt%) were investigated through melting temperature, electrical conductivity, corrosion behavior, wettability and mechanical strength. The composite samples were produced following the powder metallurgy method. The results presented for mechanical alloying demonstrate that this method was a suitable technique for dispersing MWCNT and MLG in Bi-Ag powders. Overall, MWCNT and MLG increased the melting point. The maximum melting point recorded when 0.1 wt% of nano particles was in the matrix as 272.02 °C and 269.62 °C for MWCNT and MLG, respectively. It was found that for both reinforced nano particles in the matrix, the electrical resistivity decreased; while, the effect of MWCNT on the electrical resistivity of the solder matrix was more than MLG. The maximum decrease of resistivity was observed for the sample with 0.1 wt% of nano particles which is 1.89 (μΩ.cm) for MWCNT and 2.53 (μΩ.cm) for MLG. The result showed that MWCNT and MLG improved the Bi-2.5Ag wettability. However, it was observed that MLG decreases the wetting angle more than MWCNT. The corrosion behavior of Bi-2.5Ag and its composite samples with MWCNT and MLG was investigated by an electrochemical technique. The results from Tafel plot curves which were run in three different acidic electrolytes illustrated that the corrosion rate for all the composite samples increased. Furthermore, it was deduced that the corrosion rate and passivation were the functions of the electrical conductivity of the sample, the electrical conductivity of electrolyte and the number of H+ in the corrosive electrolyte. Adding MWCNT and MLG to the Bi-2.5Ag improved the shear strength. However, it was observed that the shear stress of Bi-2.5Ag by adding MWCNT and MLG nano particles just improved to some particular weight percentages of nano particles in the matrix which were 0.07 wt% for MWCNT and 0.05 wt% for MLG. In a nutshell, adding MWCNT and MLG nano particles to Bi-2.5Ag solder matrix improved the melting behavior, electrical conductivity, wettability and shear strength but negatively impact the corrosion behavior.